2021
DOI: 10.1177/02654075211003331
|View full text |Cite
|
Sign up to set email alerts
|

Individual and relational differences in desire for touch in romantic relationships

Abstract: Although touch is common in romantic relationships and is generally beneficial, people differ in the extent to which they desire to give and receive touch. The current research identified individual and relationship characteristics that predict overall desire for touch and unique desire for overtly affectionate versus indirectly affectionate forms of touch. In both a sample of dating, engaged, and married individuals (Study 1) and a dyadic sample of married couples (Study 2), the strongest predictors of overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Last, measurement of proximity may provide an extra layer of information about the nature of physical closeness in romantic dyads. Jakubiak and colleagues have consistently demonstrated that physical touch provides benefits to romantic partners and that partners differ in their desire for touch (e.g., Jakubiak et al, 2021; Jakubiak & Feeney, 2019). An open question is whether physical touch provides additional benefit above and beyond physical closeness, and, if so, why and for whom.…”
Section: Discussionmentioning
confidence: 99%
“…Last, measurement of proximity may provide an extra layer of information about the nature of physical closeness in romantic dyads. Jakubiak and colleagues have consistently demonstrated that physical touch provides benefits to romantic partners and that partners differ in their desire for touch (e.g., Jakubiak et al, 2021; Jakubiak & Feeney, 2019). An open question is whether physical touch provides additional benefit above and beyond physical closeness, and, if so, why and for whom.…”
Section: Discussionmentioning
confidence: 99%
“…Insofar as social or affectionate touch can benefit well-being and relationship quality, more touch may help offset distress and relationship problems. Similar to variation in use of typical emotion regulation strategies (e.g., Grommisch et al, 2020), individuals’ ideal levels of touch differ (Jakubiak et al, 2021; Trotter et al, 2018), as does the strength of the association between touch and measures of well-being. Accordingly, the regulatory benefits may be most apparent for those who more strongly endorse using touch for affect regulation (TAR), an attribute that is particularly relevant in light of social distancing.…”
Section: Social Touch In Relationshipsmentioning
confidence: 99%
“…There is some indirect evidence that touch experiences covary with relationship satisfaction. People with higher relationship quality report greater desire for touch (especially intimate forms of touch), are more motivated to touch to approach positive outcomes, and are less motivated to touch to avoid negative outcomes than those with lower relationship quality (Jakubiak et al, 2021a(Jakubiak et al, , 2021b. Additionally, people with higher relationship quality report greater actual engagement in affectionate touch (Gulledge et al, 2003;Mackey et al, 2000).…”
mentioning
confidence: 99%